2016
DOI: 10.1007/s12011-016-0762-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Selenium, N-Acetylcysteine and Vitamin E Against Acute Ethanol Intoxication in Rats

Abstract: The aim of this study was to determine possible protective influences of selenium (Se), N-acetylcysteine (NAC), and vitamin E (Vit E) against acute ethanol (EtOH) intoxication. Thirty-six rats were divided into six groups: I (control), II (EtOH), III (EtOH + Se), IV (EtOH + Vit E), V (EtOH + NAC), and VI (EtOH + mix). Except group I, EtOH was given the other pretreated (groups III, IV, V, and VI) and untreated groups (group II). Compared with the EtOH group, serum aspartate aminotransferase, alanine aminotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The most common medications for ALD are classified into three categories: supplemental raw materials for liver cell metabolism [12], opioid receptor antagonists [12], and agents that manage and improve alcohol metabolism [13, 14]. However, drug dependence, vomiting, dermatitis, dizziness, and leukopenia have been observed in ALD patients after long-term treatment with these agents [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most common medications for ALD are classified into three categories: supplemental raw materials for liver cell metabolism [12], opioid receptor antagonists [12], and agents that manage and improve alcohol metabolism [13, 14]. However, drug dependence, vomiting, dermatitis, dizziness, and leukopenia have been observed in ALD patients after long-term treatment with these agents [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ozkol et al in their experimental model have shown that supplementation of selenium (alone or in combination with vitamin E and N-acetylcysteine) exerts hepatoprotective effects in rats exposed to ethanol [20]. The authors have demonstrated that the positive effects of selenium are likely to result from its antioxidative and neutralising action against free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis showed that vitamin E significantly improved liver function and histologic changes in patients with hepatic steatosis [22]. Ozkol et all showed relative protection against acute EtOH toxicity, in both single and combined pretreatments of Selenium, N-Acetylcysteine, and Vit E supplementation were seen in brain, liver, and kidney tissues, probably by antioxidant mechanism [23].…”
Section: Discussionmentioning
confidence: 99%